2022
DOI: 10.3390/su14148446
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Spatial Changes of Shiraz’s Historic District on Perceived Anti-Social Behavior

Abstract: As cities grow, their spatial configurations may undergo some changes over time. This study attempted to examine the impact of the changes that occurred to the spatial configuration of the historical district of Shiraz on perceived anti-social behavior (ASB). Space syntax techniques were used to assess whether they can explain the extent to which perceived levels of anti-social behavior were impacted by these changes. Historical and present maps of the city were obtained and spatially analyzed using DepthmapX.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…This finding is also aligned with previously conducted studies, which confirmed that an irregular spatial configuration may possess a lower value of legibility [ 91 , 92 , 93 ]. In addition, the results were found to be consistent with respect to prior studies, which affirmed that urban development can lead to decreasing levels of legibility and accessibility [ 44 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 87%
“…This finding is also aligned with previously conducted studies, which confirmed that an irregular spatial configuration may possess a lower value of legibility [ 91 , 92 , 93 ]. In addition, the results were found to be consistent with respect to prior studies, which affirmed that urban development can lead to decreasing levels of legibility and accessibility [ 44 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 87%
“…The city dates to 2000 BCE (Cameron, 1948) and is home to two UNESCO world heritage sites. Shiraz is also known for its rich history, culture, mosques and bazaars and major pilgrimage sites (Shaykh-Baygloo, 2021; Moqadam and Nubani, 2022). Many of the traditional houses of Shiraz's historical context belonged to government leaders, businessmen, clergymen and other religious and cultural figures.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, regarding research on the impacts of Spatial Morphology: Wang and Sun [66] developed a dynamic game model of traffic competition, starting from the impact of spatial form on traffic.Other scholars have focussed on the effect of spatial form on perception:Xu et al [67] investigated the relationship between street networks and tourists' spatial cognition;Mushayt et al [68] used eye-tracking to evaluate the impact of street interface physical configurations on pedestrian visual perception;Moqadam and Nubani [69] explored the impact of changes in spatial patterns on perceived anti-social behavior (ASB). Besides,Xu et al [70] analyzed cultural and urban landscapes from the perspective of spatial value;Huang et al [71] studied the impact of diversity and accessibility on street vitality; Zhu et al [72] explored the relationship between spatial morphology in severe cold historical districts and microclimates.While many studies in this category focus on the mid-level street aspects, most emphasize the impacts brought about by morphological features.…”
Section: Study On the Spatial Morphology Of Historic Districtsmentioning
confidence: 99%